Fighting for the Man in the Blue Overalls—Daily Sun as a Project in Demarginalisation. Issue 3 (3rd July 2021) - Olorunnisola, Anthony A.; Castoe, Jennifer; Han, Giana
ABSTRACT: We located the emergence of South Africa's Daily Sun against the background of colonisation of the print media and the more recent economic embeddedness of Black and alternative media in duopolistic domains. Our analyses found historical marginalisation and contemporary remarginalisation of majority Black readers useful. For theoretical frame, we relied on normative influences that make the centre more newsworthy than the periphery and some citizens outcast from the public sphere. We inferred and concluded that the Daily Sun —with all its real and perceived shortcomings—capitalised on a sectoral gap by focusing on "unknown" and abandoned citizen-readers. Its accomplishments, when not negated by criticism of its White ownership, was in the ability to demarginalise and decolonise poor Black working-class readers. Our submission included implications for theory.